P47-T Could needle EMG still be helpful in diagnosis of myotonia congenita?. Issue 7 (July 2019) - Nojszewska, Monika; Łusakowska, Anna; Gaweł, Małgorzata; Sierdziński, Janusz; Sułek, Anna; Krysa, Woiletta; Elert-Dobkowska, Ewelina; Seroka, Andrzej; Kamińska, Anna M.; Kostera-Pruszczyk, Anna
Abstract : Background: Myotonia congenita (MC) is the most common nondystrophic myotonia caused by loss of function mutations in the CLCN-1 chloride channel. Aims: The purpose of this study was to describe detailed EMG characteristics of patients with MC as well as to test the hypothesis that needle EMG could help to distinguish between the recessive and dominant form of MC. Material and methods: We evaluated 36 patients (23 men) aged 4–61 years with genetically proven MC. In 30 patients (19 men) autosomal recessive form of MC (BMC) and in 6 – autosomal dominant MC (TMC) was recognized. We analyzed EMG results for motor unit action potential (MUAP) morphology as well as the occurrence and distribution of myotonic discharges (MD). Results: were recorded in 95.8% of examined muscles, in almost 100% muscles of patients with BMC and in about 80% muscles in TMC subgroup. The were described as common (in BMC) or widespread in TMC especially in distal limb muscles (first interosseous dorsalis and tibialis anterior, TA) where differences between groups reached statistical significance. For the whole MC group we observed a statistically significant positive correlation between MUAPs parameters in vastus lateralis and TA muscles and the duration of the disease. Similar correlation for biceps brachii muscle, was found in BMC. Conclusions: This study supported the hypothesis that needle EMG could still be helpful in diagnosis of MC and together with short exercise and short exercise with cooling tests might be useful in differentiation between BMC and TMC.